Akad Jual Beli dalam Fiqih Muamalah: Studi Komparatif Fathul Qarib dan Fathul Mu’in - Arisma Damayanti; Muhammad Hamdi (Jurnal Riset Ekonomi dan Akuntansi, 2026)
This study aims to analyze and compare the concept of sale and purchase contract in Fathul Qorib and Fathul Mu’in as two important references in Islamic commercial jurisprudence within the Shafi‘i school. This research employs a qualitative approach using a library research method by examining literature relevant to the discussion of sale and purchase contracts. The findings show that both books view sale and purchase as a contract of exchanging property for property that results in the legal transfer of ownership. The validity of the contract is determined by the fulfillment of the pillars and requirements of sale and purchase, including the contracting parties, the sighat in the form of offer and acceptance, and the object of the transaction, which must be clear, lawful, beneficial, and deliverable. Fathul Qorib explains the concept of sale and purchase briefly and systematically, particularly regarding definitions, requirements of goods, prohibition of usury, khiyar, salam, rahn, and debts. Meanwhile, Fathul Mu’in provides a broader and more analytical explanation, covering the requirements of contracting parties, various forms of khiyar, prohibited transactions such as usury, ihtikar, and najasy, as well as disputes in sale and purchase. Thus, Fathul Qorib serves as a basic foundation, while Fathul Mu’in expands the discussion more applicatively. Both books complement each other in understanding sale and purchase contracts comprehensively.